Evaluation of Undergraduate Dental Students' Perspective on Distance Education Model in the Coronavirus (Covid-19) Pandemia - Gediz Geduk; Hatice Biltekin; Emre Haylaz; Çiğdem Şeker (Ankara University, 2021)
Purpose:The aim of this study is to question and evaluate the perceptions of 3rd, 4thand 5thyear undergraduate dentalstudents towards distance education practices and the roles of faculty members in the implementation of educationduring the Covid-19 pandemic.Materials amp; Methods:An online survey was applied to 149 volunteers, consisting of 3rd, 4thand 5thyear undergraduatedental students. The survey composed of 12 questions about distance education and shared from "Google Forms"application. Data analysis was done with SPSS 22.0 Packet Data Program.Results:One hundred forty-nine undergraduate dental students, including 54 third-year students, 60 fourth-yearstudents and 35 fifth-year students, answered the survey on a voluntary basis. Upon this, each answer was examinedseparately, and efforts were made to reach conclusions about the distance education model. When results were evaluated,the majority of the students (40.9%) who participated in the survey reported that the distance education modelcontributed to the theoretical lessons, when adequacy of the practical training was assessed, it was concluded thatdistance education was "Absolutely Inadequate" at with a 79.9 percentageConclusion:As a result of the study, most of the students found the distance education model sufficient for theoreticalcourses, but insufficient for practical education and found traditional practical education more advantageous